2000
DOI: 10.1159/000045731
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Metabolic Acidosis and Its Effects on Serum Parameters in Hemodialysis Patients

Abstract: We screened the laboratory data of 50 chronic hemodialysis patients selected randomly over a 21-month period to generate 158 data points which identified two groups: (1) those with a predialysis total CO2 concentration less than or equal to 19 mEq/l (data A; n = 57) and (2) those with a predialysis total CO2 concentration greater than 19 mEq/l (data B; n = 101). Then, both groups were compared for the following parameters: predialysis blood urea nitrogen (BUN), serum phosphorus, uric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 9 publications
3
9
0
1
Order By: Relevance
“…Their study suggested that persistent acidosis, observed despite standard bicarbonate dialysis, was caused by a high dietary protein intake which resulted in an increased acid load. In our group of patients, however, we could not observe this correlation, in agreement with the study by Gao et al [2], although with a much smaller number of patients in our studies. Also, the quantity of dialysis, measured by URR, did not correlate with the degree of acidosis during the pre-dialysis period, nor did the increment in URR in 7 patients individually alter subsequent bicarbonate measurements made before dialysis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Their study suggested that persistent acidosis, observed despite standard bicarbonate dialysis, was caused by a high dietary protein intake which resulted in an increased acid load. In our group of patients, however, we could not observe this correlation, in agreement with the study by Gao et al [2], although with a much smaller number of patients in our studies. Also, the quantity of dialysis, measured by URR, did not correlate with the degree of acidosis during the pre-dialysis period, nor did the increment in URR in 7 patients individually alter subsequent bicarbonate measurements made before dialysis.…”
Section: Discussionsupporting
confidence: 92%
“…For patients on HD, the highest level of total body acid load is found during the period immediately before HD, and is generated from protein nutrition and accumulated with variable intensity. The treatment of acidosis by HD has received diverse considerations [1][2][3]. Some studies show that increasing the dialysate bicarbonate concentration may decrease the degree of acidosis before HD and improve nutritional status [4,5], although in one study there was no alteration in Leite/Leal/Cardoso nutritional parameters [6].…”
Section: Introductionmentioning
confidence: 99%
“…Total protein, serum albumin, uric acid and serum phosphorus can be used as markers of better nutrition. As in previous studies by Gao et al 5 and Leavey et al 6 , we also noted an inverse correlation between BMI, total protein, serum phosphorus, serum uric acid and serum ferritin levels. This suggests that a higher protein intake may lead to a lower serum bicarbonate at the start of the subsequent dialysis session.A higherpredialysisserum bicarbonate level may be a surrogate of inadequate dietary protein intake 7 .…”
Section: Discussionsupporting
confidence: 90%
“…Gao et al [40]demonstrated that higher predialysis serum bicarbonate (predialysis total CO 2 concentration >19 mmol/l) significantly improves predialysis BUN, phosphorus, and uric acid concentrations. Graham et al [41]demonstrated better leucine turnover with correction of acidosis.…”
Section: Uremic Acidosis and Malnutritionmentioning
confidence: 99%